(untitled) (Conferencea, 2022)
This article is devoted to research of discourse and pragmatics and analyzed parts of M. Nizanov’s works linguistically. The research also points out the main structure of analyzing the contexts with regard to 4 steps including their scientific concepts. By author’s conclusion , you may understand the importance of this scientific work for the schools of English linguistics.